Jalan Menjadi Waliyullah dalam Kitab Hadis Arbain Nawawi Hadis Ke-38 - Arif Friyadi (JASNA : Journal For Aswaja Studies, 2022)
AbstractThe problems of a person's life in the world often make him depressed and hopeless. Not infrequently who have to end his life by drinking poison. That's why God gives guidance so that his heart is always calm despite the thousands of problems he faces. Provision is none other than being a waliyullah. This is  where the Prophet Muhammad through his teachings laid the foundations that a Muslim must take to become a Waliyullah (beloved of Allah) so that the life of a Muslim is more peaceful and directed. The  guidance  is  contained  in  the  38th  hadith  of  the  Book  of  Arba'in  Nawawi.  This  study  uses  a qualitative research library methodology. The author tries to explore as many sources as possible in his  writings.  With  a  literature  review,  the  author  tries  to  examinethe  39th  Book  of  Arba'in  Nawawi hadith  combined  with  existing  references  to  support  the success  of  the  research.  From this  study the author  concludes,  if  someone  wants  to  be  a  lover  of  Allah,  one  must  believe  in  Allah,  fear  Him  and carry out sunnah practices that can draw closer to Him. If this has been done, Allah will be present in his every breath, as his guardian and protector.Keywords: Waliyullah, Arba'in Nawawi Hadith, provision for becoming.AbstrakPermasalan  hidup  seorang  di  dunia  seringkali  membuat  dia  tertekan  dan  putus  asa.  Tidak  jarang yang  harus  mengakhiri  hidupnya  dengan  menenggak  racun.  Karena  itulah  Allah  memberikan tuntunan  agar  hatinya  senantiasa  tenang  meski  ribuan  permasalahan  yang  dihadapinya.  Bekal  itu tidak  lain  adalah  menjadi  waliyullah.  Di  sinilah  Nabi  Muhammad  melalui  ajarannya  meletakkan dasar-dasar  yang  harus  ditempuh  seorang  muslim  untuk  menjadi  Waliyullah  (kekasih  Allah)  agar hidup  seorang  muslim  lebih  tentram  dan  terarah.  Tuntunan  itu  tertuang  dalam  hadis  ke-38  Kitab Arba’in Nawawi. Penelitian ini menggunakan metodologi kualitatif library riset. Penulis berusaha menggali sebanyak mungkin sumber buku dalam tulisannya.Dengan kajian pustaka penulis berusaha menelaah Kitab Arba’in Nawawi hadis ke-39 dipadukan dengan referensi yang ada untuk mendukung keberhasilan  penelitian.  Dari  penelitian  ini  penulis  berkesimpulan,  jika  seorang  ingin  menjadi kekasih  Allah  haruslah  mengimani  Allah,  bertakwa  kepada-Nya  dan  menjalankan  amalan-amalan sunnah  yang  dapat  mendekatkan  diri  kepada-Nya.  Jika  ini  telah  dilaksanakan,  Allah  akan  hadir dalam setiap hembusan napasnya, sebagai penjaga dan pelindungnya.Kata kunci: Waliyullah, Hadis Arba’in Nawawi,Tuntunan Muslim.